FORM, MEANING AND FUNCTIONS OF GALA AMPEK JINIH PAGA CANCANG ETHNIC IN NAGARI KOTO BARU, SOLOK - Mahardhika, Dedek (Universitas PGRI Sumatera Barat, 2019)
The focus of this research was on dissecting gala ampek jinih of Paga Cancang ethnic in Nagari Koto Baru, Kubung Sub-District, Solok Regency. The analysis was carried out on aspects of form, meaning and functions. The location of data collection was in Nagari Koto Baru, Kubung Sub-District, Solok Regency. The approach used in this research was a descriptive qualitative approach. The data collection phase included the process of observation, interview and field notes. Furthermore, the data was transcribed from spoken language into the written one, categorized the form of gala, defined the meaning contained and examined the function of each gala. The results of data analysis indicated that there were three forms of address categories of gala ampek jinih of Cancang paga ethnic used in Nagari Koto Baru, Kubung Sub-District, Solok Regency. The forms of gala included; (1) Title plus name, (2) Title plus last name, (3) First name plus second name and (4) Title plus first name. Moreover, the delivery of meaning in this study was in the post-structuralism domain; that one word does not always have one meaning. Gala ampek jinih has its own construction of meaning based on the title position of the person. Analysis of the meaning construction reflects the function of the title itself.